Real‐time non‐intrusive RF biochemical sensor. Issue 19 (7th July 2020) - Pandit, Nidhi; Jaiswal, Rahul K.; Pathak, Nagendra P.
Abstract : In this Letter, a non‐destructive microwave resonant sensor based on the modified complementary split‐ring resonator has been proposed and analysed with respect to its sensitivity for detecting the aqueous biochemicals. This technique is based on the perturbation theory and only requires to measure resonant frequency and hence, achieving a substantial reduction in the computation time and cost. The proposed sensor is designed to achieve high sensitivity performance with a measured quality factor of the sensor in the bare state, Q B = 631.5, at the centre frequency of f o = 6.31 GHz. The proposed sensor has a maximum sensitivity of S = 6.23 MHz with respect to a unit change in the dielectric constant value. A numerical model is developed for the dielectric constant of the biochemicals as a function of the resonant frequency. The proposed sensor, therefore, provides high sensitivity, simple structure layout and real‐time response with cost effectiveness. The proposed structure can be a potential candidate for the non‐intrusive sensing of aqueous biochemicals.